Phenotype and Tissue Residency of Lymphocytes in the Murine Oral Mucosa - Park, Joo-Young; Chung, Hyunsoo; Choi, Youngnim; Park, Jung-Hyun (Frontiers in Immunology, 2017)
The oral mucosa is a critical barrier tissue that harbors a series of distinct immune cell subsets. Immune surveillance in the oral mucosa is important for both local and systemic immunity because the oral cavity is a heavily utilized route of pathogen entry and also serves as site of pathogen propagation. Nonetheless, composition and phenotype of the lymphocyte pool in the oral mucosa have remained poorly characterized. Utilizing a newly established protocol for mucosal immune cell isolation, here we report that the oral mucosa features a unique cellular composition of immune cells which differed not only from secondary lymphoid organs, but also from mucosal tissues in the gut and lung. We observed profound accumulation of CD11b+Ly6Clo monocytes in the oral mucosa that were maintained independently of T- and B-lymphocytes. Unlike the gut mucosa, the oral mucosa contained neither CD8aa T cells nor was it enriched for CD103+CD69+ tissue-resident memory CD8 T cells. In fact, a major fraction of T cells circulated and trafficked through the mucosa as revealed by treatment with the S1P1 receptor antagonist, FTY720, a potent inhibitor of lymphocyte migration. Collectively, these results provide a comprehensive picture of immune cells in the oral mucosa as an active site of lymphocyte recruitment and surveillance.